2015
DOI: 10.1352/1944-7558-120.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Strain and Sensory Features in Children With Autism Spectrum Disorder and Other Developmental Disabilities

Abstract: Caring for children with disabilities contributes to increased levels of parent stress, or caregiver strain. However, the potential relationship of sensory features to strain among caregivers of children with autism spectrum disorder (ASD) and other developmental disabilities (DD) is unknown. Sensory features include over-reactions, under-reactions, and unusual interests in sensations, which may negatively impact family functioning. This descriptive study confirmed three caregiver strain types (i.e., objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…; Kirby et al . ) although the different scales used in these studies preclude any conclusion regarding which pattern may be the best predictor of parental stress.…”
Section: Correlations Between Atypical Sensory Processing and Adaptivmentioning
confidence: 95%
See 1 more Smart Citation
“…; Kirby et al . ) although the different scales used in these studies preclude any conclusion regarding which pattern may be the best predictor of parental stress.…”
Section: Correlations Between Atypical Sensory Processing and Adaptivmentioning
confidence: 95%
“…However, there are still few studies that have directly analysed the relationship between atypical sensory processing patterns and parental stress. Specifically, using the parental stress index-short form (PSI-SF; Abidin 1995), several studies find that some specific sensory patterns are better at predicting parental stress than others (Abidin 1995;Ausderau et al 2016; Table 1 Correlations between atypical sensory processing and adaptive (and maladaptive) behaviour found in previous studies carried out with children with ASD, using the sensory profile (extended version, SP; or short version, SSP) and the VABS (or VABS-2) -Sasson et al 2013;Kirby et al 2015) although the different scales used in these studies preclude any conclusion regarding which pattern may be the best predictor of parental stress. In summary, sensory processing difficulties have been widely reported in the literature.…”
mentioning
confidence: 99%
“…Despite a growing understanding that these behaviors are embedded in—and contribute to—the daily experiences of children with ASD and their families (Dickie et al, 2009; Dunn, 2007; Kirby et al, 2015c; Schaaf et al, 2011), there has been minimal systematic exploration of the contexts surrounding sensory and repetitive behaviors. Child development theories (e.g., Ecological Systems Theory; Brofenbrenner, 1979) expound the importance of context in understanding child behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Abbeduto et al (Abbeduto et al 2004) also found that while caregivers with FXS have lower well-being than caregivers of individuals with Down Syndrome, they have better well-being than caregivers of individuals with ASD. In other studies, caregivers of individuals with ASD have been observed to experience higher levels of caregiver burden, stress, health and psychological impairment than caregivers of individuals with ADHD, or general developmental delay or behavioral impairment (Estes et al 2009, Cadman et al 2012, Kirby et al 2015). …”
mentioning
confidence: 88%
“…Caregiving for an individual with complex psychiatric, developmental or medical disorders has been shown to have a significant impact on family caregivers including higher perceived caregiver burden (Angold et al 1998, Bussing et al 2003, Iosif et al 2013, Vaughan et al 2013, Kirby et al 2015), lower quality of life (Mugno et al 2007, Kuhlthau et al 2010, Feeley et al 2014, Hoefman et al 2014), poorer physical health (Meltzer and Mindell 2006, Murphy et al 2007, Feeley et al 2014) and higher levels of depression and lower level of overall psychological well-being (Abbeduto et al 2004, Ha et al 2008, Estes et al 2009, Yamaki et al 2009). It has been shown to be correlated as well with physiological markers of stress (Lovell et al 2012a, Lovell et al 2012b, Iosif et al 2013).…”
mentioning
confidence: 99%